Finding the nexus between associative mechanisms and cocoa Farmer resilience against natural hazards in Ghana - Enoch Kwame Tham-Agyekum; Felix Kyei; John-Eudes Andivi Bakang; Henry Oppong Tuffour; Winnefred Mensah; Elsie Assan (Sustainable Environment)
Existing literature has acknowledged the vulnerability of cocoa farming to various natural hazards but there is a notable dearth of research comprehensively exploring the specific associative mechanisms that cocoa farmers employ to tackle these challenges. Employing a quantitative research approach, the investigation draws on data collected from a sample of 384 cocoa farmers who were selected using the multi-stage sampling technique. The findings reveal that religious groups are the most available associative mechanisms (86.98%) while cooperative societies emerge as a widely used associative mechanism among cocoa farmers (Mean = 4.16). The prevalence of diseases and pests (91.9%), and drought (70.3%) pose substantial threats to cocoa cultivation. In enhancing the resilience of cocoa farmers against natural hazards, associative mechanisms serve as a linchpin by providing access to timely information (Mean = 4.11). Farmers’ biggest challenge in their associative mechanisms is ‘limited support and recognition from the government or policy framework’ (Mean rank = 7.24). The insights gleaned from the research underscore the crucial role of associative mechanisms, particularly cooperative societies, in bolstering the resilience of cocoa farmers. The ability of these mechanisms to serve as conduits for information dissemination, resource pooling, and collaborative problem-solving is highlighted as instrumental in mitigating the adverse impacts of natural hazards. In this light, the study advocates for the continued support and fortification of associative mechanisms as a strategic approach to enhancing cocoa farmer resilience in the face of prevalent and emerging natural challenges.